PENINGKATAN KEMAMPUAN MENELAAH STRUKTUR FABEL DENGAN MODEL DISCOVERY LEARNING DAN MEDIA POHON TELAAH - Muammar, Muammar (Jurnal Edukasi Khatulistiwa : Pembelajaran Bahasa dan Sastra Indonesia, 2021)
ABSTRACT This study aims to describe planning, performance, and the learning assesment studying the fable text structure by applying the discovery learning model and media trees to class VII SMPN 11 Satu Atap Menukung student participants.. The method used in this study is descriptive method with qualitative forms of research. The research subject has been teacher and a class VII SMPN 11 Satu Atap Menukung Kecamatan Menukung Kabupaten Melawi with 15 participants and datas are the result teacher ability assesment 1(APKG 1), result of teacher ability assesment 2 (APKG 2), interview result, and learning result of student VII class VII SMPN 11 Satu Atap Menukung. The result shows that the overall paln for learning is increasing from cycle 1 to cycle 2. Result on the plan to implement learning acquired on the cycle 1 ends up in 79 with adequate predicate and increases on cycle 2 to 84 with a good predicate. A teacher’s performance in managing learning experiences an improvement from cycle 1 with score 82 with a good predicate and increasing on cycle 2 to 89 with a good predicate. The result shows that the average score that students earn on Learning in cycle 1 shows the average score 56 with 8 students completed apprentices (54%). The study of cycle 2 is also improving with average score 74 with 12 students completed apprentices (80%). So the learning curve studied the structure of the fable text using the discovery learning model and media of the tree learning stage of cycle 1, and cycle 2 are enhanced. Keywords : DISCOVERY LEARNING, STRUCTURE OF FABLE TEXT, TREE OF LEARNING